Children Mobile eBook Creator - Elnajjar, Mahmoud A.M. (2009)
Mobile phone contains many features and tools such as mobile camera for taking pictures and a microphone to record sounds. These tools can be innovatively utilized to enhance children creativity by building stories from their collections of pictures and audio. Furthermore, children should be able to store, manage, retrieve and index their mobile contents collections. These properties should exist in mobile system package that can also be a source of education. The aim of this study is to develop a mobile eBook application called Mobile eBook Creator. This application should help children create their own electronic story books (eStoryBooks), that can also search, retrieve, merge and index pictures, audio, video and text in mobile platform. In addition, the study also records data on how ten children ages between 7 and 11 used the functionality provided in the application. The recorded data were learning time to use the application (LT), number of question asked (No Q) and number of help required when completing tasks (No H). Furthermore, the number of tasks completed (No TC) was also noted. Generally it can be concluded that the mobile creator can be utilized without much problem by children of aged 8 years and above.